An Error Analysis of Using Punctuations in Narrative Texts - Mukhammad Isnaeni; Frans Asisi Datang (ELT-Lectura, 2017)
The objectives of this research are to find out whether the students commit punctuation errors in their narrative writing or not and to identify the types of errors which are made by the students in terms of Surface Strategy Taxonomy. This is a descriptive qualitative research. The instrument used for collecting the data is writing task in narrative text, consisting of recognition and production task. The data was, then, analyzed based on procedures used in error analysis of the descriptive approach. The results show that a number of students committed erroneous data either in recognition or production task on the use of punctuation marks in terms of omission, addition, substitution, and misplacement.